Integrasi Fonetik dan Podcast dalam Pembelajaran: Pelatihan Bagi Guru Bahasa Jerman di Daerah Istimewa Yogyakarta - Santoso, Iman; Sudarmaji; Haryati, Isti; Mulyati, Retna Endah Sri; Zahro, Diyan Fatimatuz (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2026)
Community service carried out by the PkM Team of the German Language Education Department FBSB-UNY has been carried out from May 03, 2024 to June 04, 2024. The objectives of this community service are to: (1) provide insights into knowledge and learning in German phonetics for German teachers, (2) train teachers to make Podcast media to be used in the learning process. This training activity consists of three stages, namely (1) Explanation of Phonetics in German in the form of vowels, consonants and diphthongs, (2) Introduction to Podcast that can be integrated in learning dan teaching, (3) Simulation of learning using Podcast media (4) Development of learning materials using Podcast. The results obtained from the activities of this community service program are: (1) teachers participating in this activity have knowledge about German phonetics and can apply it in learning, (2) teachers are skilled in developing and integrating Podcast in learning